PENGARUH IRINGAN MUSIK TERHADAP NILAI KECEPATAN DAN KETEPATAN MENGETIK SISTEM BUTA DENGAN MENGGUNAKAN BANTUAN PROGRAM TYPING MASTER PRO PADA MAHASISWA - Triana Prihatinta,; Srimiatun; Ika Putri Suciani (P3I Politeknik Negeri Madiun, 2018)
This study aims to determine the effect of pop music accompaniment on the speed and accuracy of typing a blind system using the help of a pro typing master program on students. Research uses simple regression analysts. The population in this study were 120 students of the 2016-2017 class of the Madiun State Polytechnic Business Administration Study Program with a total sample of 30 students. Data obtained using questionnaires and documentation. The results of this study are to prove that the accompaniment of pop music affects the speed and accuracy of typing a blind system using the help of a pro typing master program. The meaning of music accompaniment affects the speed and accuracy of typing. The harder the accompaniment music, the speed and accuracy of typing will decrease. Likewise, conversely, the music accompaniment is getting slower, so the typing speed and accuracy will get better